ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUNTARY DISCLOSURE LAPORAN TAHUNAN PERUSAHAAN - Pancawati Hardiningsih (Jurnal Bisnis dan Ekonomi, 2008)
Management have accurate information about unknown company value by externalinvestor, meaning that management generally has more complete and accurate informationcompare to outside party of the company about the company value. Voluntary disclosureinformation published by a company will possibly give information about the company in such amore detail way. This research aims to test influence of the ownership of public share, companybases, ROI, size of a company and leverage ratio towards the scope of voluntary disclosure.The research sample are 66 manufacturing companies which release voluntary disclosurein 2004 and 2005. The result of the study shows that the ownership of public share influencessignificantly the scope of voluntary disclosure in the annual report of company ( p = 0,037 <0,05). Company bases own positive influence which is significantly to the scope of voluntarydisclosure in the annual report of the company ( p = 0,029 < 0,05). Ratio of ROI probability doesnot own significant influence to the scope of voluntary disclosure in the annual report of thecompany ( p = 0,686 > 0,05). The size of the company owns positive influence and significant tothe scope of voluntary disclosure in the annual report of the company. ( p = 0,001 < 0,05) andratio of company leverage does not own significant influence to the scope of voluntary disclosurein annual the report of the company ( p = 0,129 < 0,050)Keywords: Size ,ROI, Public Ownership,Leverage,Voluntary Disclosure.